Alcohol use and its correlates in suicide attempters in a rural tertiary care teaching hospital in south India - P., Sreelatha; G., Haritha; S. S. R., Ryali V.; P., Janakiraman (International Journal of Research in Medical Sciences, 2019)
Background: The relationship of alcohol and suicide is well documented. The interactions of alcohol use and suicide are complex. Neurobiological, genetic, psychological, social, cultural, and environmental factors are postulated to influence the outcome Aim was to find the frequency of alcohol use in suicide attempters and evaluate the association of alcohol use and its correlates in subjects who use alcohol to facilitate the attempt. Methods: It is a cross sectional observational study set in rural background in south India. Consecutive referrals of suicide attempters (n=175) were selected for the study. Details regarding the socio-demographic profile, suicide related details like lethality, intent, suicidal ideation, previous attempts, and alcohol related details like frequency, quantity and age at onset of alcohol consumption were recorded. Statistical significance of various socio demographic and clinical variables in correlation with use to facilitate attempt were analyzed. Logistic regression was used to determine the predictors in this at risk group of suicide attempters. Results: Over 43.43% of suicide attempters consumed alcohol. Intentional alcohol use prior to attempt to facilitate the attempt group constitutes about 18.29 %. High suicide intent and previous suicide attempt emerged as risk factors when alcohol was used to facilitate the attempt. Conclusions: Determinants, which increase the risk of suicide with alcohol use in rural south India, were identified.